A comparative study on ultrasound guided percutaneous aspiration versus incision and drainage in the management of small breast abscesses - Voruganti, Mohan R.; Sistu, Manoj K.; Gadipudi, Hamika C. (International Surgery Journal, 2022)
Background: A breast abscess is either lactational or non-lactational with the former being more common. Lactational breast abscess is more common in younger age and primipara. It occurs mostly during the first 6 weeks of lactation. A non-lactating breast abscess is usually secondary to diabetes, tuberculosis, smoking, or an underlying breast pathology. Traditional treatment of breast abscess is by incision & drainage. It causes a lot of psychological pressure on already stressed lactating mothers. Recent trends for the treatment of small breast abscesses favor minimally invasive procedure using needle aspiration under USG guidance with adjuvant antibiotics. It is now the preferred mode of treatment for small breast abscess over open surgical incision and drainage. Methods: A comparative prospective study of 50 cases of small breast abscesses less than 5cm was done using both surgery and aspiration. 25 cases were studied in each group. Follow up was done and results were tabulated. Results: Aspiration shows better results. It has the advantage of treatment under local anesthesia as a day case. Recovery (92%) is as good as open surgery. Healing is without a scar and does not need painful dressings. The drawbacks are sometimes it needs repeated aspirations and not suitable for large abscesses. Conclusions: Aspiration under ultrasonographic guidance should be first line of treatment for small (<5cm) breast abscesses.